A Novel Approach for Chronic Obstructive Pulmonary Disease Diagnosis with TensorFlow-Based Image Analysis - Agrawal, Krishna Kant; S. R., Ashwini; Singh, Sakuldeep; Saini, Rashmi; Singh, Gurwinder; Lamba, Vikas; Bhati, Nitesh Singh (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper introduces an innovative approach to Chronic Obstructive Pulmonary Disease (COPD) detection through image processing, complemented by a user-friendly web application. Leveraging TensorFlow-based CNNs, the proposed system facilitates comprehensive chest X-ray analysis. The Accuracy, precision Recall and F1 score of the proposed architecture are respectively, 94.29, 93.58, 90.47 and 91.22. The workflow involves dataset loading, preprocessing, and iterative model fine-tuning. Crucially, the web application's interface enables seamless image uploads, result displays, and collaborative discussions among healthcare professionals. By merging advanced image processing techniques with accessibility, this work envisions a future where COPD detection is not only technologically sophisticated but also user-centric, promoting effective collaboration in healthcare settings.